Evaluating The Implementation of The Newa Concept To Sustain Hotel Occupancy at Sanctoo Suites & Villas - I Putu Subali Adi Putra; Ni Made Ernawati; I Gede Mudana; I Ketut Suparta; I Ketut Suja (International Journal of Travel, Hospitality and Events, 2024)
Purpose: This research examines implementing the NEWA concept to maintain occupancy at Sanctoo Suites & Villas. The hotel industry faces significant challenges sustaining occupancy levels due to fluctuating demand and intense competition, exacerbated by the COVID-19 pandemic. The research originates from the need to enhance occupancy rates, which are critical for the hotel's success. It addresses the problem of fluctuating occupancy rates and aims to develop effective improvement strategies. Research methods: This mixed-method research employs a qualitative approach supplemented by quantitative methods and the Servqual model, conducted over six months. Data collection methods include interviews, surveys, observations, document studies, and Focus Group Discussions (FGDs) involving executive management and hotel staff. Results and discussion: The research highlights a unique marketing concept aimed at delivering new extraordinary experiences while maintaining guest satisfaction. It underscores the importance of a comprehensive approach integrating high-quality service and innovative offerings to meet diverse guest needs. This strategy enhances the hotel’s market competitiveness and ensures long-term success. Key components of the implementation include personalized guest experiences, an efficient booking system, and a proactive marketing strategy emphasizing the NEWA (Nature et al. & Adventure) concept. Implication: The findings demonstrate that implementing NEWA can significantly benefit hotel occupancy, providing valuable insights for industry practitioners.